Application of the CARE guideline as reporting standard in the Annals of Joint - Office, Editorial (Annals of Joint; Vol 4 (November 2019): Annals of Joint, 2019)
The Annals of Joint welcomes case reports which are supposed to report new observations of diseases, clinical findings or novel/unique treatment outcomes relevant to practitioners in the fields of medicine.